Membangun Ekonomi & Bisnis Pasca Pademi Covid-19 Untuk Mensejahterakan Warga Negara Indonesia - Evi, Margaretha; Ramdhani, Ridwan Faizal; Ardianto, Risna (CV. ITTC INDONESIA, 2021)
2020 has been a difficult year for the world due to the impact of the coronavirus (COVID-19) outbreak. The corona virus changed everything, first appearing locally in Wuhan, China, then spreading and destroying the foundations of the world economy. This virus has significant implications for all fields of economy, tourism, medicine, employment, religion, society, politics, and so on. The real impact of the virus outbreak is felt in all countries, including Indonesia. Covid-19 is actually a health problem. However, the impact is not only on the health side but also on the economic side, and has a major impact on social life. The impact of the Covid-19 pandemic is a major problem for the Indonesian economy because the high unemployment rate causes unemployment. Covid-19 has made the Indonesian economy give so much influence in various sectors. One of the sectors that was affected and felt so much was the economic sector. The government is trying to continue to restore and improve the slump, especially in the economic sector in Indonesia. What the government can do in rebuilding the economy and business after the Covid-19 pandemic is by carrying out several processes such as Planning, Organizing, Actuating and Controlling. Providing social assistance for business actors, tax incentives, loan relaxation, providing working capital, providing product buffers, coupled with long-term and short-term strategies such as handling Covid-19.